Alcoholism and American healthcare: The case for a patient safety approach. Issue 5 (October 2022) - Zipperer, Lorri; Ryan, Ruth; Jones, Barbara
Alcoholism, more professionally termed alcohol use disorder (AUD), is a widespread and costly behavioral health condition. The aims of this paper are draw attention to systemic gaps in care for patients with AUD and advocate for patient safety leaders to partner with both the mainstream medical and substance abuse treatment communities to reduce harm in this patient population. The authors performed a narrative review of the literature on the current state of AUD treatment and patient safety, finding extensive evidence that patients with AUD usually go undiagnosed, unreferred and untreated. When they do receive AUD treatment, little evidence was found to indicate that a patient safety approach is incorporated into their care. Behavioral medicine is virgin territory for the patient safety movement. Medical care and behavioral medicine in the United States currently constitute two separate and unequal systems generally lacking in pathways of communication or care coordination for AUD patients. Significant barriers include institutional culture, individual and systemic bias against those with AUD, and health care infrastructure, especially the separation of medical and behavioral treatment. It is the authors' conclusion that care of patients with AUD is unsafe. We advocate for the patient safety approach common in American hospitals to be extended to AUD treatment. Experienced patient safety leaders are in the strongest position to initiate collaboration between the mainstream medical and substance abuse treatment communities to reduce harm for this patient population.